The Influence of the Permian-Triassic Magmatism in the Tunguska Basin, Siberia on the Regional Floristic Biota of the Permian-Triassic Transition in the Region - Davydov, V. I.; Karasev, E. V. (Frontiers in Earth Science, 2021)
The end-Permian extinction event (EPEE) considered to have been caused by the eruption of the Siberian Large Igneous Province (SLIP), the age of which is critical for extinction-SLIP model evaluation. The Tunguska Basin flora during this time, in accordance with the EPEE model, supposed to have been killed by the massive injection into the atmosphere of poisonous substances such as methane, sulfates, mercury and massive combastion of coals. In addition, supposed numerous fires presumably devastated the regional flora. However, the diversity of the Tunguska Basin flora drasticly increased at the beginning of Induan or slightly earlier and become diverse at the species level in the Olenekian and Anisian, when the main phase of basalt eruption and associated intrusive activity occurred. The overall magmatic activity during the latest Permian and Early Triassic did not kill the flora, but rather stimulate their diversity. The geomagnetic secular variations from the intrusions revealed the similarity of paleomagnetic directions of the Norilsk group layered intrusions with those of the upper Olenekian and lower Anisian Mokulaev and Kharaelakh volcanic formations and intrusions of the Talnakh group with the Olenekian Moronga-Mokulaev formations. The U-Pb dates and the geomagnetic secular variations data expose the obvious discrepancy between these two datasets. The paleomagnetic data suggest that the Norilsk-1 intrusion is younger than the Talnakn and Kharaelakh intrusions, but the U-Pb dates indicate the opposite. The data from layered intrusions in Norilsk and the other regions suggest their prolonged duration and multi-stadial formation. The U-Pb dates from the intrusions of the Norilsk region roughly constrain the onset of the SLIP and generally postdate the end-Permian extinction.